2010
DOI: 10.1186/1471-2164-11-698
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiling of the transcriptional response to iron restriction in six serotypes of Actinobacillus pleuropneumoniae with different virulence potential

Abstract: BackgroundComparative analysis of gene expression among serotypes within a species can provide valuable information on important differences between related genomes. For the pig lung pathogen Actinobacillus pleuropneumoniae, 15 serotypes with a considerable variation in virulence potential and immunogenicity have been identified. This serotypic diversity can only partly be explained by amount of capsule and differences in the RTX toxin genes in their genomes. Iron acquisition in vivo is an important bacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 72 publications
5
15
0
Order By: Relevance
“…3b), and showed that iron deficit was able to induce the expression of feo and ycl. These results are consistent with previous reports that describe up-regulation of a system related to iron uptake (Baichoo et al 2002;Klitgaard et al 2010) and reveal some of the mechanisms employed by E. faecalis to face changes in iron availability.…”
Section: (Colour Online)]supporting
confidence: 93%
“…3b), and showed that iron deficit was able to induce the expression of feo and ycl. These results are consistent with previous reports that describe up-regulation of a system related to iron uptake (Baichoo et al 2002;Klitgaard et al 2010) and reveal some of the mechanisms employed by E. faecalis to face changes in iron availability.…”
Section: (Colour Online)]supporting
confidence: 93%
“…This is another argument that confirms the validity of our microarray 363 17 results, as already described in similar works (Allen et al 2010;Klitgaard et al 2010; 364 Vasileva et al 2012). 365…”
Section: Discussion 340supporting
confidence: 90%
“…The range of log 2 fold changes was apparently low, ranging between 357 1.78 and -2.13, but the numbers obtained were in general quite similar to those observed for 358 transcriptomic analyses of iron starvation in other microorganisms (Allen et al 2010; Basler 359 et al 2006;Brickman et al 2011;Klitgaard et al 2010;Madsen et al 2006). However, very 360 interestingly the changes observed in our work were in most cases for genes grouped in 361 operons, and genes belonging to the same operon underwent, as expected, almost identical 362…”
Section: Discussion 340supporting
confidence: 69%
“…pleuropneumoniae genome [ 32 ]. In a recent study, genes encoding a putative enterobactin receptor system and a cirA like siderophore have been identified to be up-regulated under iron-restricted conditions [ 33 , 44 ]. These known and/or putative iron-acquisition systems might have roles in catecholamine-induced growth of A .…”
Section: Discussionmentioning
confidence: 99%